2018
DOI: 10.5194/acp-18-3289-2018
|View full text |Cite
|
Sign up to set email alerts
|

Different trends in extreme and median surface aerosol extinction coefficients over China inferred from quality-controlled visibility data

Abstract: Abstract. Although the temporal changes in aerosol properties have been widely investigated, the majority of studies has focused on average conditions without much emphasis on the extremes. However, the latter can be more important in terms of human health and climate change. This study uses a previously validated, quality-controlled visibility dataset to investigate the long-term trends (expressed in terms of relative changes) in extreme surface aerosol extinction coefficient (AEC) over China and compares the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…8 and S7), the decadal trends of MERRA-2 agreed better with the trend results from MODIS and MISR. This implies that the trends can change relatively quickly with time (Li et al, 2018). Sup- Figure 9.…”
Section: Regional Aod Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 and S7), the decadal trends of MERRA-2 agreed better with the trend results from MODIS and MISR. This implies that the trends can change relatively quickly with time (Li et al, 2018). Sup- Figure 9.…”
Section: Regional Aod Trendsmentioning
confidence: 99%
“…Finally, to better quantify the relative contributions of each independent explanatory variable, which were obtained from the stepwise MLR model, to AOD variability, the LMG method (Bi, 2012;Grömping, 2006;Lindeman et al, 2014) was applied. This approach is one of the most advanced methods for determining the relative importance of explanatory variables in a linear model and provides a decomposition of the fraction of model-explained contributions (i.e., R 2 ) into nonnegative contributions using semi-partial R values.…”
Section: Trend Analysis and Stepwise Mlr Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The Beijing-Tianjin-Hebei (BTH) region, which is one of the most densely populated economic zones in China, has considerably high levels of PM 2.5 (Jiang et al, 2015;Chen and Wang, 2015). During severe winter haze days (SWHDs), the detected daily mean PM 2.5 concentrations reached 300-600 µg m −3 in BTH (Wang et al, 2014a;Li et al, 2018b). Exposure to these fine particulate matters detrimentally affects human health, causing problems from respiratory illnesses to cardiovascular diseases and premature death (Lelieveld et al, 2015;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Fu et al (2013) defined an extremely poor visibility event as a case with atmospheric visibility of less than 5 km for at least 3 days and found that the annual frequency of such event averaged over large cites in China (142 cities with populations of more than one million) increased from 1960 to 2009 with a trend of 0.68 events decade -1 . Using the visibility-converted daily aerosol extinction coefficient (AEC) dataset, Li et al (2018a) examined the long-term trends in extremely high AEC (the 95 th percentile in a year) at 272 sites in China and compared these trends with the trends in median AEC (the 50 th percentile in a year). They showed that the extreme trends exceeded the median trends at most sites in the 1980s, the extreme trends were larger than the median trends in the south (south of 33° N) but smaller in the north (north of 33° N) in the 1990s, and then, most sites exhibited a faster increase in the median trends in the 2000s.…”
mentioning
confidence: 99%